Comparison of Body Size, Morphomics, and Kidney Function as Covariates of High‐Dose Methotrexate Clearance in Obese Adults with Primary Central Nervous System Lymphoma. Issue 4 (27th March 2020) - Pai, Manjunath P.; Debacker, Kenneth C.; Derstine, Brian; Sullivan, June; Su, Grace L.; Wang, Stewart C.
Abstract : Background: High‐dose methotrexate (HD‐MTX) is used to treat primary central nervous system lymphoma (PCNSL), but potential differences in MTX clearance (CL) due to obesity have not been studied. We characterized the relationship between HD‐MTX CL and computed tomography (CT)‐generated body composition (morphomic), body size descriptors, and laboratory measurements in a cohort of obese and non‐obese patients with PCNSL. Methods: Medical records from adult patients with PCNSL treated with HD‐MTX over a 10‐year period were queried. Individuals with CT data within 30 days of the first cycle of treatment were included. Population pharmacokinetic analysis was performed using a 2‐compartment base structural model. We specifically compared body surface area (BSA) to standard body size, morphomic, and renal function estimation methods as covariates of HD‐MTX CL. Results: The final data set consisted of non‐obese (n=45) and obese (n=28) patients with 291 observations (3–7 samples per patient) with a mean (standard deviation) weight of 69.8 (11.6) kg and 104 (14.9) kg, respectively (p=0.0001). Vertebral body height was more informative than BSA of MTX CL. Similarly, a CL model incorporating age, albumin, and serum creatinine was more informative than kidney function equations and body size. The final model of MTX CL was based on age, albumin, serum creatinine, and vertebral body height. Conclusions: Common clinical variables coupled with vertebral body height are more predictive of first cycle MTX CL than BSA, alternate body size descriptors, and commonly used kidney function equations.